Attitude to Elderly Individuals Visibility: Politics VS Fashion - Belova, Alla (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article highlights the verbal packaging of attitude to visibility of older people in politics and fashion – the two professional fields marked by unrivaled visibility and exceptional interest of the public. Statistics, gerontolinguisitcs, multiple reports reveal the greying of the world, the skyrocketing propotion of people 65+, with the soaring share of octogenarians. Nevertheless, elderly individuals remain invisible in public places, workplaces, being excluded from decision-making process. In the 21st century visibility of the elderly becomes a component of inclusive societies and sustainable development. Age limitations keep people of retirement age out of employment in many fields but outstanding professionals in their eighties break age stereotypes and remain active, stealing the limelight due to their extraordinary talent and exceptionalism. Gerontocracy in the US politics in the 2010-2020s is being severely criticised in mass media and gets lots of negative comments on social media. Gerontocracy has crept into the White House, Congress, The Supreme Court where octogenarians are obsessed with workism, nonagenarians cling to power. The articles on US political gerontocracy are marked by obvious negative sentiment, usage of age-related idioms, words with the negative evaluative meaning. Vice versa, senior models catwalking at prestigious fashion shows and invited to luxury brands advertising campaigns are perceived positively as the embodiment of taste, elegance and a healthy way of life. Laudatory articles about clothes-wise mature female models – successful actresses, singers, writers – have positive sentiment. Age-related words (wrinkle, grey) are used in the articles about fashion in a positive context. Brilliant careers of octogenarian and nonagenarian politicians are neglected in the articles while the past achievements of senior models are presented in the advantageous way.